2004
DOI: 10.1523/jneurosci.1766-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Long-Term Potentiation Suppressed by Increased Inhibition in the Ts65Dn Mouse, a Genetic Model of Down Syndrome

Abstract: Although many genetic disorders are characterized by cognitive failure during development, there is little insight into the neurobiological basis for the abnormalities. Down syndrome (DS), a disorder caused by the presence of three copies of chromosome 21 (trisomy 21), is characterized by impairments in learning and memory attributable to dysfunction of the hippocampus. We explored the cellular basis for these abnormalities in Ts65Dn mice, a genetic model for DS. Although basal synaptic transmission in the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
404
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 435 publications
(429 citation statements)
references
References 54 publications
21
404
1
3
Order By: Relevance
“…Studies in DS mouse models have shown impaired synaptic efficacy because of increased inhibition (40,43), which is potentially caused by overproduction of inhibitory interneurons at the expense of glutamatergic projection neurons (44). However, we found no significant difference in the ratio of excitatory to inhibitory sPSCs (Fig.…”
Section: Ds Neurons Are Deficient In Their Ability To Form Functionalmentioning
confidence: 51%
See 2 more Smart Citations
“…Studies in DS mouse models have shown impaired synaptic efficacy because of increased inhibition (40,43), which is potentially caused by overproduction of inhibitory interneurons at the expense of glutamatergic projection neurons (44). However, we found no significant difference in the ratio of excitatory to inhibitory sPSCs (Fig.…”
Section: Ds Neurons Are Deficient In Their Ability To Form Functionalmentioning
confidence: 51%
“…Recent studies in DS mouse models have put forth the hypothesis that an imbalance in the excitation-inhibition ratio may underlie ID in DS. Results have shown impaired synaptic efficacy because of increased inhibition in various brain regions (40,43), potentially caused by overproduction of inhibitory interneurons that primarily originate from the ventral forebrain, at the expense of glutamatergic projection neurons (44). Synaptic deficits in humans have been inferred from ultrastructural studies showing abnormal dendritic spine morphology (23,55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…167 A major functional synaptic defect detectable in Ts65Dn mice is the failure to induce LTP in the hippocampus. [168][169][170][171] This deficit has been attributed to excessive inhibition, 171 a hypothesis recently confirmed by Fernandez et al, 172 which showed that the spatial learning disabilities observed in Ts65Dn mice are rescued by administration of non-competitive antagonists of GABAA receptors. The impairment in synaptic plasticity is linked to marked morphological changes in the structure of synapses, with a selective enlargement of the active zones of asymmetric synapses and increased immunostaining for synaptic proteins marking inhibitory synapses.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 86%
“…In addition, the imperfect association of ACh markers with behavior may also reflect independent consequences of age in the partial trisomy mice, for example in other neurotransmitters (Fernandez et al, 2007) or neurobiological processes. These other processes include impaired long-term potentiation (Costa and Grybko, 2005;Fernandez et al, 2007;Kleschevnikov et al, 2004;Siarey et al, 1997), enhanced long-term depression (Siarey et al, 1999), impaired expression of brainderived neurotrophic factor (Seo and Isacson, 2005), altered signaling pathways (Siarey et al, 2006), and altered neuroanatomical organization of the hippocampus Hanson et al, 2007;Kurt et al, 2004;Lorenzi and Reeves, 2006).…”
Section: General Conclusionmentioning
confidence: 99%